2018
DOI: 10.1155/2018/9120878
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Procalcitonin for Bacterial Infection after Transarterial Chemoembolization or Radiofrequency Ablation for Hepatocellular Carcinoma

Abstract: This prospective observational study aimed at investigating the role of procalcitonin (PCT) in diagnosing bacterial infection and guiding antibiotic therapy for hepatocellular carcinoma (HCC) patients with fever after transarterial chemoembolization (TACE) and/or radiofrequency ablation (RFA). Ninety-seven cases (84 patients) were enrolled. Serum PCT, C-reactive protein (CRP), and white blood cell (WBC) counts were measured on the day of fever onset (day 0) and days 1, 3, 5, and 7 of fever. Empirical antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In the context of comparing the diagnostic accuracy of PCT and CRP in detection of bacterial infection in our cohort, the ROC curve revealed that PCT had higher sensitivity and specificity regarding prediction of bacterial infection with sensitivity of 100% and specificity of 100%, while CRP can predict bacterial infection with sensitivity of 90% and specificity of 92.5%, with significant area under the ROC curve for both of them; this agrees with many reports in the literature [ 19 - 24 , 26 - 28 ], which emphasizes the superiority of PCT over CRP regarding presence of bacterial infection in terms of higher sensitivity and specificity. Combining both PCT and CRP would have synergistic predictive value.…”
Section: Discussionsupporting
confidence: 91%
“…In the context of comparing the diagnostic accuracy of PCT and CRP in detection of bacterial infection in our cohort, the ROC curve revealed that PCT had higher sensitivity and specificity regarding prediction of bacterial infection with sensitivity of 100% and specificity of 100%, while CRP can predict bacterial infection with sensitivity of 90% and specificity of 92.5%, with significant area under the ROC curve for both of them; this agrees with many reports in the literature [ 19 - 24 , 26 - 28 ], which emphasizes the superiority of PCT over CRP regarding presence of bacterial infection in terms of higher sensitivity and specificity. Combining both PCT and CRP would have synergistic predictive value.…”
Section: Discussionsupporting
confidence: 91%
“…TACE procedures have been regarded as minimally invasive with a good curative profile and strong repeatability; thus, it is mostly used in the nonsurgical treatment of HCC. However, the chance of occurrence of infection is always there, which results will not only prolong the hospital stay and expenses but also will affect the efficacy of treatment [ 13 ]. Moreover, the majority of the TACE-treated patients are middle-aged, or they are in the advanced stage of cancer where the immune system is less active, coupled with damage to nearby tissues caused by operation and the anticancer drugs' immune function inhibition leading to postoperative infection [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%